Ni–Mo nanoparticles stabilized by ether functionalized ionic polymer: A novel and efficient catalyst for hydrodeoxygenation of 4-methylanisole as a representative of lignin-derived pyrolysis bio-oils. (6th January 2021) - Saidi, Majid; Safaripour, Maryam
Abstract: In the present study, nickel-molybdenum nanoparticles stabilized with ether functionalized ionic polymer were synthesized and utilized as a novel and efficient catalyst for hydrodeoxygenation of 4-methylanisole as a representative of lignin-derived bio-oil. The catalytic upgrading process was performed in the presence of hydrogen with a batch reactor at temperature of 80–200 °C, hydrogen pressure of 10–50 bar, reaction time of 0.5–15 h and catalyst loading of 1–5 mol%. The major reaction classes during 4-methylanisole upgrading were hydrodeoxygenation and hydrogenolysis which resulted in production of 4-methylphenol, toluene, phenol and benzene as the main products. The experimental results indicated that the catalytic activity of Ni–Mo (20%–80%) nanoparticles stabilized with ionic polymer is superior to that with low Mo content. Also, it is observed that the selectivity of deoxygenated products including toluene and benzene improves with increasing the Mo content of the catalyst. Finally, regarding to the excellent catalytic activity of synthesized nanocatalyst during upgrading process of bio-oil at mild operating condition, ether functionalized ionic polymer was introduced as an applicable and effective stabilizers for nickel-molybdenum nanoparticles. Highlights: Upgrading of lignin-derived bio-oil into valuable fuels has been studied. Ni–Mo NPs stabilized by ether-functionalized IP have been synthesized. Ni–Mo NPs have been demonstrated superior activities in HDO of 4-methylanisole. Sensitivity analysis of operating parameters have been considered. Ether functionalized IP is introduced as an effective stabilizer for Ni–Mo NPs.